Penerapan Kebijakan Kedisiplinan dalam Program Tahfidz di MIS Pesisir Selatan - Rendy Nugraha Frasandy; Rafi Firdaus (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This research aims to; knowing the implementation of disciplinary policies in the implementation of the tahfiz program at MIS Pesisir Selatan. This research is packaged with a qualitative descriptive research design, where the data sources are tahfiz teachers, school principals, and students at MIS Pesisir Selatan. In collecting data, the writer uses observation, interview, and documentation techniques. To analyze the data the author uses inductive, deductive and comparative methods. The results showed that the disciplinary policy in the tahfiz program at MIS Pesisir Selatan was divided into 3, firstly disciplined on time, such as: students arrived on time, that is, before tahfidz started, they arrived at the place, if there were students who were late for the tahfidz event, they directly faced the principal with asked carefully the reason is often late. Sanctions for students who are late are enough with a warning, if it is still carried out, the sanctions are discussed in deliberation by the principal and teachers, so that the punishment can be deterMIS Pesisir Selataned according to the actions that have been done. The two disciplines enforce the rules, such as teachers, students and parents/guardians using uniforms that are polite, neat and clean, not wearing sandals on top of the mosque. The three disciplines are in attitudes such as speaking politely and politely, raising your hand when you want to speak and starting and closing the study by praying.